Effect of Acetic Acid and/or Sodium Hydroxide Treatment towards Characters of Wonosari Natural Zeolite for Hydrotreatment of Castor Oil into Biofuel - Triyono Triyono; Wega Trisunaryanti; Iip Izul Falah; Lailatul Rahmi (Universitas Gadjah Mada, 2023)
Natural zeolite (ZA) obtained from Wonosari, Indonesia, was treated with acetic acid (ZAA) or NaOH (ZAB), and the combination of both treatments (ZAAB) in order to increase the Si/Al ratio and catalytic performance on hydrotreatment of castor oil. The Si/Al ratio of ZA increased after the combination of acetic acid and NaOH treatment. The change of the Si/Al ratio was observed in the FTIR spectra as the shifting of internal asymmetric stretching vibration of T−O−T at 1032-1100 cm−1. The XRD profile of ZA was maintained after being subjected to treatments, and ZAB exhibited the lowest crystallinity. The surface area of the ZA after treatment is in the order ZAA < ZA < ZAAB < ZAB. The ZAB catalyst having the highest surface area (19.144 m2 g−1) showed the highest catalytic activity on the hydrotreatment of castor oil with a liquid fraction of 55.1 wt.% and selectivity towards the hydrocarbon compounds of 22.40 wt.%.